Perancangan Program Sistem Informasi Dokumen Kontrol Proyek - Sifa Nur Utami; Normah Normah (Jurnal Manajamen Informatika Jayakarta, 2023)
In the current era of globalization, increasingly sophisticated technology, one of which is a website that is used as a means of communication to increase value by using internet facilities. So, using a website in addition to simplifying and speeding up work, it also saves a lot of time and money. One example of the problem that the author takes is the Design of a Project Control Document Information System. Good project documentation or recording is needed by the company so that the monitoring project can run well. PT. Alfatama Sukses Cipta is a mechanical and electrical contractor company which in its implementation still records project documents manually and is not well organized. Therefore, the authors here want to help simplify the project control document system by making an online application. So, by making this project control document application, the authors hope it can help to simplify and speed up the project document monitoring process.